Development of The Application for Car Audio Parts Detection Damage Using Case Based Reasoning Method and Nearest Neighbor Algorithm - Andika Saputra; Ali Khumaidi (Jurnal Teknik Informatika C.I.T Medicom, 2021)
PT. Denso Ten often receives car audio spare parts that are damaged due to shocks during the trip or sender's error. Damaged parts are collected and repaired by maintenance who has special skills manually. The limited number of maintenance operators and the frequent transfer of experts resulted in work delays due to insufficient spare parts. Spare parts repair work cannot be done by all employees because it requires special skills. The Case-based Reasoning approach and Nearest Neighbor algorithm are used to be developed for expert systems to support the detection of audio part damage so that it will speed up work and can be done by employees without special knowledge. The system can run and be used by users properly as needed and the results have good accuracy. The Case Base Reasoning method and the nearest neighbor algorithm work according to the rules and the calculation results are according to the expert's results.